Determination and reduced life expectancy model and molecular docking analyses of estrogenic potentials of 17β-estradiol, bisphenol A and nonylphenol on expression of vitellogenin gene (vtg1) in zebrafish. (April 2019) - Chen, Hualong; Zhao, Ling; Yu, Qiming Jimmy
Abstract: This study determined and evaluated the estrogenic potentials on hepatic vitellogenin gene ( vtg1 ) of adult male zebrafish which were exposed to low level concentrations (ng/L-μg/L levels) of individual and binary mixtures of 17β-estradiol (E2 ), bisphenol A (BPA) and nonylphenol (NP) through the use of reduced life expectancy (RLE) model and molecular docking analysis. The order of in vivo estrogenic potentials of individual and binary exposure of E2, BPA and NP was as follows: E2 +BPA＞E2 ＞E2 +NP＞BPA＞BPA + NP >>>NP. Binary mixtures of E2, BPA and NP had weak synergistic effects under the exposure concentration ranges. With the expression of hepatic vtg1 gene, the hepatic toxicity was analyzed by using the RLE model. All plots of the linear RLE model had negative slopes indicating that EC50 was negatively correlated with the natural logarithm of exposure time (ln ET 50 ). The RLE model analyses can be useful to evaluate the exposure time effects of zebrafish by using EC50 as toxicity endpoint. Molecular docking analysis revealed that the interaction potential of E2 (Binding energy: −10.1 kcal/mol) for the zebrafish ERα-LBD was the most potent (stable), followed by BPA (−8.0 kcal/mol) and NP (−6.8 kcal/mol). Molecular docking analysis can be useful to understand interactive effects of E2, BPA and NP. Graphical abstract: Image 10 Highlights: Binary mixtures of E2, BPA and NP have weak synergistic effects on hepatic vtg1 gene of zebrafish. The RLE model for lethal toxicity was extended to study the effect of exposure time on EC50 of vtg1 levels. A new interpretation for interaction potential of binary mixtures of E2, BPA and NP was given through molecular docking.